EPIDEMIOLOGICAL MONITORING OF AVIAN INFLUENZA IN THE REPUBLIC OF CRIMEA - D. V. Gadzevich; S. I. Danilchenko; S. G. Yerofeyev; M. A. Pasunkina; A. B. Grinchenko; V. N. Irza; M. S. Volkov; A. V. Varkentin (Ветеринария сегодня, 2019)
The paper presents the results of monitoring tests performed in the FGBI “ARRIAH” Branch in 2018 to detect AIV circulation in the Republic of Crimea. As AIVs are most frequently detected in aquatic and semiaquatic birds wild waterfowl present the greatest threat of the disease introduction and spread. That’s why the paper gives special attention to the Azov Sea and Sivash water area and describes natural biotopes of the Central and Eastern Sivash. During expeditions biological material samples were collected, bird species were identified and bird fauna was estimated in waterfowl aggregation sites. Laboratory PCR tests of the biological material collected during the expedition as well from killed birds and poultry revealed no AIV type A. As the number of wildfowl in the their usual aggregation sites decreased due to the fact that fresh water supply through the North-Crimean Canal ceased it can be assumed that the Crimean peninsula will manage to maintain HPAI freedom despite the fact that the disease is being reported close to the peninsula. Nevertheless, the threat of the virus introduction to the commercial and backyard farm stocks still exists as the peninsula is located in the bird migration routes and AI epidemical monitoring is a topical task.